Implementasi Sistem Online Single Submission Risk Basic Approach (OSS RBA) dalam Meningkatkan Kualitas Pelayanan Pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kabupaten Aceh Tamiang - Muhammad Syarif; Budi Hartono; Isnaini Isnaini (Mahesa Research Center, 2023)
The purpose of this study was to analyze implementation and what factors influence the implementation of the Online Submission Risk Basic Approach (OSS RBA) system in improving the quality of service at the Investment and One-Stop Services Office of Aceh Tamiang Regency. To analyze implementation, Edward III's theory was used, among others, namely communication, resources, disposition and bureaucratic structure This research is a qualitative research, which produces descriptive data from data in the field. The data collection process was carried out by researchers through three data collection techniques, namely: observation, in-depth interviews, documentation study. The results of the study found that in the implementation of the application, the implementation was quite good, in terms of the communication that was carried out. Human resources and budget, not yet sufficient. Disposition, is in accordance with the regulations and provisions of its implementation and is in accordance with the applicable SOP. The inhibiting factor is the lack of outreach to the community as business actors; Lack of implementing staff or human resources implementing the OSS RBA application system; Budget resources that are still limited so that they cannot meet the facilities and infrastructure for the OSS RBA application system services; The rules change frequently which makes it difficult for employees to keep abreast of developments.